Program Induksi Guru Pemula di Sekolah Dasar - Arif Nofa Sugiyanto; Sutama; Murfiah Dewi Wulandari (Elementary Teacher Education Program, Majalengka University, 2023)
The existence of novice teachers starting to teach at school makes it necessary to implement a mentoring program for novice teachers. This research aims to describe the planning, implementation and control of the Beginner Teacher Induction Program. The type of research is qualitative ethnography. The research subjects were school principals, school supervisors, guidance teachers and novice teachers at Wonogiri Regency State Elementary Schools. Data collection techniques using interviews, observation and document analysis. Validity of data by triangulation of sources and techniques. Data analysis technique using the flow method. The data analysis process involves data collection, data reduction, display, verification and drawing conclusions. The research results show that the novice teacher induction program has run well. At the planning stage, activities are carried out to analyze the needs of novice teachers, determine participants, prepare guidebooks, appoint supervising teachers, prepare mentoring schedules and monitoring schedules. The implementation stage contains guidance activities consisting of guidance on the preparation of learning plans, guidance on implementation of learning, guidance on assessment of learning outcomes, improvement of learning, enrichment of material, and implementation of other relevant tasks. Control is carried out by school supervisors in implementation monitoring, coaching and assessment activities. Management of a beginner teacher induction program that is structured systematically and in a focused manner can enable novice teachers to adapt to the work environment and novice teachers can improve their competence as professional teachers. The existence of novice teachers starting to teach at school makes it necessary to implement a mentoring program for novice teachers. This research aims to describe the planning, implementation and control of the Beginner Teacher Induction Program. The type of research is qualitative ethnography. The research subjects were school principals, school supervisors, guidance teachers and novice teachers at Wonogiri Regency State Elementary Schools. Data collection techniques using interviews, observation and document analysis. Validity of data by triangulation of sources and techniques. Data analysis technique using the flow method. The data analysis process involves data collection, data reduction, display, verification and drawing conclusions. The research results show that the novice teacher induction program has run well. At the planning stage, activities are carried out to analyze the needs of novice teachers, determine participants, prepare guidebooks, appoint supervising teachers, prepare mentoring schedules and monitoring schedules. The implementation stage contains guidance activities consisting of guidance on the preparation of learning plans, guidance on implementation of learning, guidance on assessment of learning outcomes, improvement of learning, enrichment of material, and implementation of other relevant tasks. Control is carried out by school supervisors in implementation monitoring, coaching and assessment activities. Management of a beginner teacher induction program that is structured systematically and in a focused manner can enable novice teachers to adapt to the work environment and novice teachers can improve their competence as professional teachers.